Emotional competence, styles of coping with stressful situations, anxiety and personality traits in judokas - Mitic, P. (Serbian Journal of Sports Sciences, 2011)
Research into the psychological characteristics of judokas is not common in sport psychology. This study aimed to examine the differences in the prominence of multiple psychological variables between top judokas and recreational athletes. We examined: emotional competence, anxiety, types of coping with stress, neuroticism, extroversion, aggressiveness, openness and conscientiousness. The participants were top competitors of the Kinezis Judo Club and individuals who often did sports but only recreationally. The obtained results revealed that judokas had more pronounced emotional competence, especially in governing emotions; besides, they were less anxious and neurotic, i.e., they used the task-oriented coping strategy when coping with stress. Not only do the results indicate that it is possible to create a set of psychological predictors of success in judo, but they also provide insight into the very nature of this particular sport. The restriction of this research refers to the sample, which is highly selective albeit of a small number.